Syntheses, crystal structures, and luminescent properties of three metal coordination polymers based on adipic acid and 2-(pyridine-3-yl)-(1H)-benzimidazole - Wang, C.C.; Wang, J.H.; Tang, G.M.; Wang, Y.T.; Cui, Y.Z.; Ng, S.W. (Taylor & Francis, 2015)
Three new metal coordination polymers constructed from adipic acid and 2-(pyridin-3-yl)-(1H)-benzimidazole ligands, [M(ADP)(3PBI)2(H2O)2]·2H2O (M = Ni and Co for 1 and 2, respectively) and [Cd(ADP)(3PBI)(H2O)] (3) [ADP = adipic acid dianion; 3PBI = 2-(pyridin-3-yl)-(1H)-benzimidazole], have been synthesized by hydrothermal reactions and were characterized by X-ray single-crystal diffraction, elemental analyses, IR, powder X-ray diffraction, and thermogravimetry. Complexes 1 and 2 are isostructural. Both form a 1-D linear chain structure, which is further assembled into a 3-D supramolecular framework by ππ stacking and hydrogen bonding interactions. Complex 3 possesses a binuclear unit and displays a 2-D layer which is further extended to a 3-D supramolecular architecture via hydrogen bonding and other weak packing interactions. The luminescent properties of 3 were investigated in the solid state at room temperature.